PENGARUH KELOMPOK REFERENSI, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PADA PRODUK SUSU FORMULA NESTLE LACTOGROW DI KOTA PEKANBARU - Sagala Putri Indah Nancy; Zulkarnain Zulkarnain; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of Reference Group, ProductQuality and Promotion on Buying Decision and Costumer Satisfaction in usingNestle Lactogrow Formula Milk in Pekanbaru City. The population in this studyincludes all consumers who buy and use Nestle Lactogrow Formula Milk inPekanbaru City, while totally samples in this study is 100 people. The samplingtechnique in this study is Purposive Sampling, which is the selection of samplesbased on certain criteria. Data taken from respondents using questioners. Theanalytical method used in this research is path analysis using SPSS (StatisticalPackage for Social Science) aplication. The result show that: (1) ReferenceGroup has significant effect on Buying Decision. (2) Product Quality hassignificant effect on Buying Decision. (3) Promotion has significant effect onBuying Decision. (4) Buying Decision has significant effect on CustomerSatisfaction. (5) Reference Group has significant effect on Customer Satisfactionthrough Buying Decision as a variable intervening. (6) Product Quality hassignificant effect on Customer Satisfaction through Buying Decision as a variableintervening, and (7) Promotion has significant effect on Customer Satisfactionthrough Buying Decision as a variable intervening in using Nestle LactogrowFormula Milk in Pekanbaru City.Keywords : Refererence Group, Product Quality, Promotion, Buying Decision andCustomer Satisfaction